Connecting - Helen Walker; Louise Morgan; Amy Wink; Marcia Nell; Gergana Vitanova; Judy Huddleston (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
Louise Morgan—Street Science: An English Teacher’s Introduction to Street Life. Amy Wink—'In the Middle of Difficulty Lies Opportunity'— Albert Einstein Marcia Nell—The New Partnership Gergana Vitanova—Negotiating an Identity in Graduate School as a Second Language Speaker. Judy Huddleston—A Cat in the Sun: Reflections on Teaching.